Pemberdayaan UMKM di Desa Lebakwangi Melalui Optimalisasi Google My Business, Sosialisasi Sadar K3 dan Seminar Digital Marketing - Fikhri Farhan Mobarok; Hasbi Hasidik Sihab; Tirta Nida Nurfadillah; Neng Asri Nurul Azizah; Rafika Ratik Srimurni (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program was implemented in Desa Lebakwangi to empower 25 SMEs through the optimization of Google My Business, Occupational Health and Safety (OHS) awareness, and digital marketing seminars. The program aimed to improve the online visibility of SMEs, raise awareness of OHS, and enhance understanding of digital marketing strategies. The method included 3 training sessions per topic, 4 weeks of mentoring, and performance evaluations based on technology adoption and OHS compliance indicators. The results showed that 80% of SMEs successfully optimized Google My Business, with an average 40% increase in online interactions. The OHS awareness campaign improved compliance with safety procedures by 35%, based on initial and final surveys. The digital marketing seminar increased participants' understanding of digital marketing strategies, with an average 30% improvement in comprehension scores, from 60% to 90%. Additionally, the program demonstrated a positive impact on SMEs' income, with estimated increases of 20% to 30% following the adoption of digital technology and OHS practices. This program provided tangible solutions for SME development in the digital era, with enhanced competitiveness and better implementation of OHS procedures. The implication of this activity highlights the importance of continuing the program to ensure sustainable positive impacts.